Bridging mechanisms of through-thickness reinforcement in dynamic mode I&II delamination - Cui, Hao; Yasaee, Mehdi; Kalwak, Gordon; Pellegrino, Antonio; Partridge, Ivana K.; Hallett, Stephen R.; Allegri, Giuliano; Petrinic, Nik (Elsevier, 2017)
Z-pin through-thickness reinforcement is used to improve the impact resistance of composite structures; however, the effect of loading rate on Z-pin behaviour is not well understood. The dynamic response of Z-pins in mode I and II delamination of quasi-isotropic IM7/8552 laminates was characterized experimentally in this work. Z-pinned samples were loaded at both quasi-static and dynamic rates, up to a separation velocity of 12 m/s. The efficiency of Z-pins in mode I delamination decreased with loading rate, which was mainly due to the change in the pin misalignment, the failure surface morphology and to inertia. The Z-pins failed at small displacements in the mode II loading experiments, resulting in much lower energy dissipation in comparison with the mode I case. The total energy dissipation decreased with increasing loading rate, while enhanced interfacial friction due to failed pins may be largely responsible for the higher energy dissipation in quasi-static experiments.
Keywords: Z-pin; Mode I; Mode II; Delamination; Dynamic